New Baby Welcoming Celebration in Saluan and Korea - Hardianti Hardianti; Sulistiyani Sulistiyani (English Education Study Program, 2020)
Every culture has its way to celebrate the appearance of a new family member. This study provides some information related to the new baby welcoming celebration of two different cultures: Saluan and Korea. This qualitative study finds some similarities within the celebration as well as their values behind. The differences found in the case of time and the number of events included in the celebration. Hopefully, with the rise of understanding of the two cultures, the appreciation and affection towards local cultures can also be improved. Keywords: New Baby Welcoming Celebration; Saluan; Korea.